“Reread me backwards”: Deciphering the Past in Elizabeth Bowen’s The Heat of the Day - Johnson, Stephanie (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2016)
Set during the midst of the London Blitz, Elizabeth Bowen’s The Heat of the Day revolves around a narrative of espionage, but unlike many novels from the spy genre, it refuses to disclose all of its secrets. Instead, the novel’s dense and complex language, which so effectively expresses the dislocating effects of a city under attack, resists an easy or uncomplicated reading. This article examines the motif of reading within the novel, which manifests when its protagonist, Stella Rodney, learns her lover Robert is a Nazi spy. In her efforts to locate proof of his defection, Stella becomes caught in a recurrent but indeterminable task of rereading past events, a movement which attempts to remember the past but also foregrounds a fundamental inability to ever wholly resolve its enigmas. When Stella fails to read her past for lost clues, she is prevented from viewing the events of her life as a coherent and meaningful narrative. The novel’s difficult language reflects this lack of resolution, refusing to assimilate the events it depicts into a straightforward account. With its wartime setting as a disorienting backdrop, The Heat of the Day undermines the purpose of reading as the discovery of sense and meaning, producing instead only more questions and mysteries.